Development and Validation of e-Modules Integrated with PBL and Local Wisdom to Enhance Critical Thinking and Problem-Solving Skills - Syarful Annam; Agus Ramdani; Muh. Makhrus; Yusuf Sarkingobir (Pedagogy Review, 2024)
Abstract: This study develops and validates e-modules incorporating Problem-Based Learning (PBL) and local wisdom to enhance students' critical thinking and problem-solving skills. As 21st-century education emphasizes the integration of technology and innovative strategies, these e-modules aim to support higher-order thinking while preserving cultural values amidst globalization. The research specifically focuses on the topic of Temperature and Heat for Grade VII junior high school science education. Using a Research and Development (RD) approach based on the 4D model Define, Design, Develop, and Disseminate this study completes the development stage, including validation and preliminary testing. In the Define stage, a needs analysis identified that traditional teacher-centered methods inadequately develop students' critical thinking skills. The Design stage systematically structured the e-modules with reflective activities, interactive problem-solving exercises, and integration of local wisdom, leveraging Flip PDF Professional for engaging content creation. The e-modules underwent validation by three expert validators, who evaluated content, presentation, and language. Results showed a validity score exceeding 80% across all criteria, classified as "very valid." A preliminary test involving 30 Grade VII students employed a pre-test and post-test design. The analysis revealed a significant improvement in student performance, with the mean pre-test score of 60.25 increasing to a post-test mean of 85.75 (42.4% improvement). Statistical analysis using a paired ttest yielded a p-value of 0.001 (p 0.05), confirming the e-modules' effectiveness. Additionally, the incorporation of local wisdom within the PBL framework was positively received, promoting cultural appreciation alongside cognitive skill development. In conclusion, the developed Flip PDF-based e-modules satisfy highquality educational standards and effectively enhance students' critical thinking and problem-solving skills. Their integration of technology and local cultural values positions them as impactful tools for junior high school science education.   Keywords: e-module, problem-based learning, local wisdom, critical thinking, problem-solving.